The relation between depressive symptoms and age among older Europeans: Findings from SHARE - Isabella Buber; Henriette Engelhardt (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2008)
Empirical evidence on the effects of age on mental health is diverse. Therefore, the paper aims to analyze the association between age and the prevalence of symptoms of depression. Based on SHARE, depressive symptoms of 28,069 persons from eleven European countries and Israel aged 50 to 84 years were analyzed using EURO-D. Multivariate regression models were applied to analyze the effect of age on depressive symptoms under control of socio-economic characteristics and health. The results indicate that EURO-D scores increased with age and were higher among women compared to men. When controlled by socio-demographic characteristics and health conditions the association between depressive symptoms and age almost vanished. The association between depression and age is driven by socio-demographic characteristics and the physical as well as cognitive health of older persons. Once controlled for these sociodemographic characteristics, age no longer had an important explanatory power on the mental health of older persons.
Keywords: 300; Mental health; depressive symptoms; age; elderly; SHARE; Altersgruppe; Psychische Störung; Alte Menschen; EU-Staaten